Tariffs in a Dynamic Differentiated Duopoly - Beverly J. Lapham (Queen's University, Department of Economics, 1991)
The effects of an unilateral tariff on prices, quantities, and welfare in the presence of a dynamic elements facing imperfectly competitive firms is examined. International duopolists, selling differentiated products, interact strategically in price setting game under the tariff policy. It is shown that the presence of dynamic elements in the form of adjustment costs to changing sales volume significantly affect the relationship between tariff rates and aggregate domestic welfare even when sales are constant and no adjustment costs are actually paid. The level of optimal tariffs is associated with higher adjustment costs. Of particular interest is the possibility that autarky is optimal under positive adjustment costs while tariff restricted trade is optimal in the absence of such costs.
Keywords: 330